Fashion Trends and Social Media: Why are Influencers the Key to the Success of Batik Muthidea Products on Instagram? - Mawardi, Moh. Cholid; Sudarmiatin, Sudarmiatin (International Journal of Advanced Multidisciplinary, 2024)
This study aims to determine and analyze the simultaneous and partial influence of Influencers and Endorsements on Purchase Intention of Muthidea Fashion Products on Instagram Social Media. This type of research is explanatory. Data was collected using a questionnaire distributed via Google Form, with a sample consisting of 154 respondents who had purchased Muthidea fashion items through Instagram within the past three months. The data analysis employed Descriptive Statistics and Multiple Linear Regression techniques. Findings indicate that both influencers and endorsements have a significant simultaneous effect on the Purchase Intention for Muthidea Fashion on Instagram. This suggests that any increase in Influencer presence or Endorsement will lead to a corresponding rise in Purchase Intention. Specifically, Influencers significantly affect Purchase Intention, indicating that a higher number of engaged followers and unique fashion content can boost Purchase Intention. Similarly, Endorsements also play a crucial role in influencing Purchase Intention, meaning that enhancing the credibility, expertise, and capabilities of celebrity endorsers will further elevate Purchase Intention.